Leptophlebiidae (Insecta: Ephemeroptera) ocorrentes no Estado do Rio de Janeiro: taxonomia e caracterização biológica das ninfas - Silva, Elidiomar Ribeiro da (2002)
The leptophlebiids from Rio de Janeiro State are still poorly known from fawlistic, taxonornic and biological points of view. Until this moment, ten genera of the family Leptophlebiidae were recorded in tbis State: Askola Peters, 1969, Farrodes Peters, 1971, Hagenulopsis Ulmer, 1920, Hermanella Needbam & Murphy, 1924, Hylister Domínguez & Flowers, 1989, Massartella Lestage, 1930, Miroculis Edmunds Jr, 1963, Needhamella Domínguez & Flowers, 1989, Perissophlebiodes Savage, 1983, and Thraulodes Ulmer, 1920. Herein is presented a survey of the nymphs of Leptophlebiidae from several places of Rio de Janeiro State. Taxonomic studies revealed the occurrence of nine new species, two of then in Massartella (bolh from Nova Friburgo), one in Hermanella (from Itatiaia), one in leentvaaria Demoulin, 1966 (from Comendador Levy Gasparian), one in Needhamella (from Comendador Levy Gasparian), one in Thraulodes (from Itatiaia), one in Traverella Edmunds Jr, 1948 (from Comendador Levy Gasparian), one in Ulmeritoides Traver, 1959 (from Teresópolis), and one in an undesctibed genus (from Teresópolis). Nymphs of Fãrrodes carioca Domínguez, Molineri & Peters, 1996 (from Comendador Levy Gasparian, Itatiaia, Macaé, Mangaratiba, Nova Friburgo, and Teresópolis), Thraulodes itatiajanus Traver & Echnunds Jr, 1967 (from Angra dos Reis, Itatiaia, Mangaratiba, Nova Friburgo, Parati, and Teresópolis), and Massartella alegrettae Uhner, 1943 (from Teresópolis) are described for the first time. Nymphs of Askola froehlichi Peters, 1969 (from Angra dos Reis, Itatiaia, Nova Friburgo, and Teresópolis), Hylister plaumanni Domínguez & Flowers, 1989 (from Cachoeiras de Macacu, Nova Friburgo, Petrópolis, and Teresópolis), Massartella brieni (Lestage, 1924) (from Angra dos Reis, Itatiaia, Mangaratiba, Nova Friburgo, Rio de Janeiro, and Teresópolis), and Miroculis froehlichi Savage & Peters, 1983 (from Angra dos Reis, Cachoeiras de Macacu, Casimiro de Abreu, Comendador Levy Gasparian, Itatiaia, Macaé, Mangaratiba, Nova Friburgo, Rio de Janeiro, and Teresópolis) are redescribed. Leentvaaria, Traverella, Ulmeritoides, and the new genus are for the first time recorded in Rio de Janeiro State. Rio de Janeiro becomes the Brazilian state with the major registered number of genera of Leptophlebiidae (fourteen genera). Most of the genera and species of this family are related to rithral habitats, occupying places with deposition of aloctone organic matter.